Sosialisasi Penyakit Populer dikalangan muda-mudi melalui Penerapan Pola Hidup Sehat - Ratna Mildawati; Ary Kristijono; Fendy Prasetyawan; Yuneka Saristiana; Bandhi Prasetya Nugroho (Jurnal Pengabdian Kepada Masyarakat Al-Amin, 2024)
Joint disease is a non-communicable disease that is often experienced by teenagers and middle-aged people. This disease is mostly suffered by the age group over 15 years which causes various complications. The aim of this program is to increase public knowledge, especially teenagers and middle-aged people, and understanding of gout and cholesterol, especially regarding how to prevent it, so that it can help improve the quality of public health. The method of this activity is carried out by means of online and offline education and socialization which is carried out in three stages. The first stage is preparation of activities, the second stage is implementation of activities, and the third stage is implementation of evaluation activities and preparation of reports. The implementation of this activity includes the stages of providing material, question and answer and ending with a posttest. The results after being given the material and the posttest showed an increase in knowledge and understanding about popular diseases according to the posttest score. It is hoped that this socialization will be able to prevent popular diseases that most young people experience, so that it can improve the quality of public health.